Politics of the developing areas (Princeton, 1970)
In a lengthy introductory essay, Gabriel A. Almond develops a conceptual framework within which different political systems may be studied. Succeeding essays utilize many of his functional categories. They are uniformly excellent. This is an outstanding work which will yield a rich harvest to student and specialist.
Keywords: Political Science